2017
DOI: 10.1016/j.ssmph.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and correlates of suicidal behaviours (ideation, plan and attempt) among adolescents in senior high schools in Ghana

Abstract: Suicide is recognised as the third leading cause of death among adolescents globally. There is however limited data on the prevalence and factors associated with suicide particularly in Ghana. To explore the prevalence and risk and protective factors associated with suicide in Ghana, a nationwide Global School-based Student Health Survey data collected among senior high school adolescents in Ghana was used. The prevalence of suicidal behaviours was 18.2%, 22.5% and 22.2% for suicidal ideation, suicidal plan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
130
5
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 47 publications
34
130
5
8
Order By: Relevance
“…The overall lifetime prevalence estimates of suicide ideation (15.4%; female = 16.2%; male = 7.1%), plans (6.6%; female = 6.9%; male = 3.6%), threats (13.4%; female = 14.1%; male = 7.1%) and attempts (2.3%; female = 2.2%; male = 3.6%) and the 12-month prevalence estimate of suicide ideation (21.3%; female = 21.7%; male = 17.9%) reported in this study are generally comparable to those found in high-income countries, with more females than males reporting suicidal behaviour.. The 12-month prevalence estimate of suicide ideation found in this study (21.3%) is comparable and quite consistent with the recent prevalence estimates among senior high school students in Ghana-18.2% (Asante et al, 2017;Baiden et al, 2019). More pointedly, the findings on the prevalence estimates of suicidal behaviour in this study are consistent with the global situation as found in the meta-analysis by .…”
Section: Prevalence Of Suicidal Behavioursupporting
confidence: 89%
See 3 more Smart Citations
“…The overall lifetime prevalence estimates of suicide ideation (15.4%; female = 16.2%; male = 7.1%), plans (6.6%; female = 6.9%; male = 3.6%), threats (13.4%; female = 14.1%; male = 7.1%) and attempts (2.3%; female = 2.2%; male = 3.6%) and the 12-month prevalence estimate of suicide ideation (21.3%; female = 21.7%; male = 17.9%) reported in this study are generally comparable to those found in high-income countries, with more females than males reporting suicidal behaviour.. The 12-month prevalence estimate of suicide ideation found in this study (21.3%) is comparable and quite consistent with the recent prevalence estimates among senior high school students in Ghana-18.2% (Asante et al, 2017;Baiden et al, 2019). More pointedly, the findings on the prevalence estimates of suicidal behaviour in this study are consistent with the global situation as found in the meta-analysis by .…”
Section: Prevalence Of Suicidal Behavioursupporting
confidence: 89%
“…Thus far in Ghana, only three published primary studies are available on the prevalence and correlates of suicidal behaviour among senior high school (SHS) students (Asante et al, 2017;Baiden et al, 2019;Liu, Huang, & Liu, 2018), with no published study on the phenomenon among (nursing and midwifery) college students, although media reports are showing worrying trends of suicidal deaths among students across the country . A college in Ghana is an immediate post-senior high school level/stage of education.…”
Section: More Recently In the Who World Mental Health Internationalmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have linked suicidal ideation in adolescents to victimization (being bullied and physically attacked) (Barzilay et al, 2017;Mahfoud, Afifi, Haddad, & DeJong, 2011;Oppong Asante, Kugbey, Osafo, Quarshie, & Sarfo, 2017), psychological factors (depressive symptoms, feeling lonely and worried) (Strandheim et al, 2014;Ziaei et al, 2017;Peltzer & Pengpid, 2012), peer relations (having no close friends) (Mahfoud et al, 2011), lack of parental understanding (Peltzer & Pengpid, 2012;Mahfoud et al, 2011), and behavioral factors (cigarette smoking and missing school without permission) (Peltzer & Pengpid, 2012;Mahfoud et al, 2011).…”
Section: Introductionmentioning
confidence: 99%